Spatial channel modeling for MIMO underwater wireless optical links - Xiaoqian LIU; Xinke TANG; Yuhan DONG (Dianxin kexue)
Underwater wireless optical communication (UWOC) has been widely used in the construction of underwater communication network for the advantages of high data rates, small latency, high flexibility and scalability.However, due to the absorption and scattering effects of seawater, the spatial characteristics of UWOC links have not been studied extensively, especially in multiple-input multiple-output (MIMO) scenario.A linear array MIMO UWOC link geometry was considered and a weighted exponential function polynomial (WEFP) model was proposed to characterize the photon irradiance distribution at the receiving plane of general MIMO UWOC links with arbitrary numbers of light sources.Numerical results suggest that the proposed WEFP model fits well with the results of Monte Carlo simulations in turbid water environment.